The use of protein supplements in children with cerebral palsy: A scoping literature review - Ineke Verreydt; Els Ortibus; Anja Van Campenhout; Kaat Desloovere; Daisy Rymen (PLoS ONE, 2025)
The aim of this scoping review was to examine the literature regarding the use of protein supplements to improve macroscopic muscle properties in a pediatric population in general, and more specifically in children with cerebral palsy. Based on our prospectively registered protocol (https://doi.org/10.17605/OSF.IO/8DM9G), a systematic literature search was performed in five databases and two clinical registers. Studies were selected by two independent reviewers using predefined selection criteria, and data were summarized using a data extraction form. A broader search on adults with cerebral palsy and the general pediatric population was considered to be relevant due to the limited number of studies conducted in children with cerebral palsy. After deduplication, 5207 records were identified and screened. A total of 18 publications were included in the current review. Two studies were performed in individuals with cerebral palsy, eight in healthy children, two in children with respiratory problems, one in critically ill children, one in children with end-stage liver disease, one in children and adolescents undergoing treatment for a pediatric malignancy, one in children with Pompe disease and two in children with Duchenne muscular dystrophy. The different muscle parameters reported were muscle volume, muscle mass, fat-free mass and fat-free mass index, lean body mass and lean body mass percentage, arm muscle area and muscle cross-sectional area of the arm, thigh and calf. The heterogeneity of the included studies and their moderate quality level made it difficult to draw solid overall conclusions. More research is needed on the use of protein supplements in children with cerebral palsy. However, supplementation with branched-chain amino acids, in particular leucine, might be promising.